PERANCANGAN DAN PENGEMBANGAN MESIN PERONTOK BULU AYAM SEMI OTOMATIS DENGAN METODE REBA (RAPID ENTIRE BODY ASSESSMENT) DIDESA BANDAR - Antoni Yohanes; Asmoro Dwi Nugroho (Jurnal Ilmiah Dinamika Teknik, 2018)
Small and medium enterprises are businesses that require small capital and small profits. One of the obstacles faced by small and medium enterprises is the lack of equipments. This happens in the traditional chicken slaughtering of Bandar village, Batang, which still uses manual labor in the process of removing chicken feathers. To overcome these problems then conducted research to design a tool in the form of thresher machine chicken feathers that can help the process of threshing fur chicken.Machine design using anthropometry and ergonomics approach and work posture analysis with REBA (rapid throughout body assessment) method. The anthropometric data used are hip height, shoulder width, hip to shoulder, and hand reach. The data has been obtained then test data uniformity, data adequacy test, and percentile determination. The REBA scores on manual removal are 5 with medium risk level which means action is needed to reduce the risk of work.The result of this research is in the form of design of work facility in the form of thresher machine of semi-automatic fur chicken adapted to body dimension. Analysis of work posture with REBA method re-done when using thresher feathers chicken, the result REBA score is 3 with low risk level. The machine is tested directly at the chicken-cutting business, and the result of the machine works quite well. Workers can throw chicken feathers easily and quickly. This machine is also considered very helpful in threshing chicken feathers compared with the previous manual process.Keywords: Rapid Entire Body Assessment (REBA), Anthropometry, Product Design, Ergonomics